Penyusunan Program yang Efektif : Menyusun Redaksi dan Menentukan Penanggung Jawab yang Tepat - Arobi Zulkurnain; Dita Noviyanti; Ummi Mardiyah (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Preparing effective programs is an important aspect in ensuring the success of an organization. This process includes formulating a program editorial that is clear, systematic and easy to understand as well as determining the person in charge in accordance with the competencies and tasks given. This research discusses how to prepare an efficient program editorial, starting from identifying goals to developing appropriate strategies. Apart from that, selecting a person in charge who has the capability to run the program is also a key factor for success. With structured editorial and optimal distribution of responsibilities, the program can run more effectively, efficiently and according to the targets that have been set. The method used in this research is literature study using journals, books and research relevant to the title. The results of the research are to provide understanding or guidance in designing strategies and programs so that they can be implemented optimally in various fields. By studying this article, researchers hope that this research will be able to open the horizons of knowledge for its readers.